Formation of Independent Thinking Skills in Youth is a Current Task of Education and Upbringing - Rakhmanova Yulduz Kakhramanovna (Researchparks Publishing, 2022)
The article highlights topical issues of education and upbringing, the need to develop independent thinking skills among young people, as well as the development and implementation of effective organizational, pedagogical forms and means of spiritual and moral education of the younger generation, based on rich national, spiritual, historical traditions, customs and universal values people.